Effects of Educative Materials on Doctors' Intention to Initiate Life-Saving Procedures After a Suicide Attempt: Randomised Controlled Trial - Braun, Marlies; Niederkrotenthaler, Thomas (Frontiers in Psychology, 2021)
Introduction The topic of euthanasia, assisted dying, and how to deal with death wishes has received strong public and media attention in many countries. Nevertheless, there is currently no research which has analysed if educative materials that favour or disfavour the initiation of life-saving measures after a suicide attempt impact on attitudes to initiate such procedures among physicians. Materials and Methods A double-blind randomized controlled trial was conducted to test if educative materials that either support life-saving measures or rather recommend against it after a near-fatal suicide attempt has an effect on intentions to initiate such measures (trial registration: DRKS00024953, www.drks.de). N = 192 doctors from the Medical University Vienna (Austria) participated in the study and either read educative materials not recommending (n = 59), or recommending life-saving measures (n = 64), or were not reading educative materials (n = 69, control group). The primary outcome was intentions to initiate life-saving measures in an open case vignette featuring the case of a terminally ill cancer patient. Other variables assessed were demographics, experiences with terminally ill and dying patients, training or qualification in mental health, specialty, position, whether doctors worked in emergency medicine, and attitudes towards assisted dying. A logistic regression analysis was used. Results There was no immediate effect of educative materials on intentions to initiate life-saving measures, χ2(2) = 0.94, p = 0.63. The adjusted model including all tested predictors was significant (χ2(15) = 37.82, df = 15, p < 0.001). Attending position, male gender, low age, and more negative attitudes to assisted dying predicted a decision for life-saving measures. Higher agreement with life-saving measures was reported for a case vignette about a patient with schizophrenia than for a case vignette about a patient with Huntington’s disease. Discussion Educative materials either favouring or disfavouring the initiation of life-saving measures after a suicide attempt do not appear to immediately influence related decision-making processes. Related intentions appear mainly influenced by personal opinions on the topic and by the specific patient case. Good-quality in-depth discussions regarding end-of-life decisions and to develop well-founded and non-opinionated guidelines are highly warranted.